The motifs of death and resurrection in Neil Gaiman’s works - Irina RAȚĂ (ACROSS)
Renowned for his reliance on the rich literary tradition in the form of references to poetry, prose, and popular culture, Neil Gaiman reimagines and reinterprets sources from myth and traditional folklore and modern, contemporary folklore to meet his own ends and match new contexts. He recycles certain themes, motifs, and symbols throughout his oeuvre. This article aims to address death and resurrection motifs, and their associated symbolism in terms of thematic criticism and structuralism, in view of determining their function at the level of the literary text